2004
DOI: 10.1051/vetres:2003042
|View full text |Cite
|
Sign up to set email alerts
|

Tritrichomonas foetus: a scanning electron microscopy study of erythrocyte adhesion associated with hemolytic activity

Abstract: -The in vitro hemolytic activity of Tritrichomonas foetus was investigated. The parasite was tested against human erythrocytes of groups A, B, AB, and O, and against erythrocytes of nine adult animals of different species (the rabbit, rat, chicken, cat, dog, swine, horse, bovine, and sheep). The results showed that T. foetus strains (ATCC KV1, K, PAL, 5022, RJ, 90) did not present any hemolytic activity against any human erythrocyte group nor against rabbit, rat, chicken, cat, dog and swine erythrocytes. T. fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…From a structural viewpoint, it is defined as a cell surce organelle formed by the plasma membrane and exterlly associated carbohydrates. Studies that focus on tricomo-ds-host cell interaction have shown that the cytotoxicity of T. foetus can be triggered from physical contact beeen the surfaces of the parasite and host cell, resulting in the secretion of extracellular proteases and glycosidases [20][21][22]. Such enzymes, in turn, seem not only to induce cytolysis or the disruption of epithelial junctions, but to remodel the surrounding extracellular matrix (ECM) [23].…”
Section: Particular Point the Cell Surfacementioning
confidence: 99%
“…From a structural viewpoint, it is defined as a cell surce organelle formed by the plasma membrane and exterlly associated carbohydrates. Studies that focus on tricomo-ds-host cell interaction have shown that the cytotoxicity of T. foetus can be triggered from physical contact beeen the surfaces of the parasite and host cell, resulting in the secretion of extracellular proteases and glycosidases [20][21][22]. Such enzymes, in turn, seem not only to induce cytolysis or the disruption of epithelial junctions, but to remodel the surrounding extracellular matrix (ECM) [23].…”
Section: Particular Point the Cell Surfacementioning
confidence: 99%